Młodzież w świecie multimedialnej manipulacji - Ćwikliński, Andrzej (Studia Edukacyjne, 2021)
The study deals with the issue of young people functioning in the world of multimedia manipulation. Alongside the undoubtedly important role of the media for contemporary education, media manipulation of young people is becoming more and more common. The text contains various definitions of manipulation and presents its types and techniques, mechanisms and goals.